Upaya Program Pos Pemberdayaan Keluarga (POSDAYA) dalam Pengentasan Kemiskinan - Devi S., L.V. Ratna (Universitas Muhammadiyah Sidoarjo, 2013)
The HDI of Indonesian society is still low. The establishment of Presidential Instruction No. 3 of 2010 has opened up new horizons that poverty reduction is prioritized by family empowerment. Field of the action is designed to touch the whole family, whether they still have a toddler, teenager, or an adult, elderly, or have a disabled family. Mentoring is done to move these families. These assistance functions are expected to someday make these families independent. The trick is to lift the mutual help and care for others by family empowerment, namely the family that is able to help other families who are poor. It is a main program in improving the welfare of society. Similarly, what are done by students who follow KKN-PPM as Posdaya mentors are intended to arouse public awareness of mutual caring. Although still seen limping but it seems people have started to be able to do. They participate in planning, implementing, evaluating, and then learning again, and it seems attractive to people who are in 3 Posdaya assisted by students. The three Posdaya are Ngudi Rahayu, Lestari and Sukamaju, all of which located in the Sambi village, Samba district, Boyolali regency.